Past, present, and future in the context of queer ageing: a qualitative study with same-sex couples in Scotland - Dora Jandric (International Journal of Ageing and Later Life)
This paper explores imagined futures of same-sex couples in Scotland through the intersection of their age and queer identities, focusing on the concepts of queer time and chrononormativity. The paper draws on qualitative interview data gathered through two joint semi-structured interviews with seven same-sex couples, and written accounts that the couples produced between the interviews. The paper demonstrates how these couples belong to the future and use their actions and knowledge to construct it. The paper contributes to ageing and future studies by exploring the queer ageing experience and the intersectionality of sexuality and age in the construction and imagination of the future. By exploring the social, cultural, and personal experiences of aging among queer adults, the findings of this paper contribute to the international discourse on aging and sexuality.